Investigation of ceramic natural ventilation using modified stoneware body for potiential application in terrace house / Mohd Fadhi Yakub - Yakub, Mohd Fadhi (2016)
Globally, the energy demand has increasingly from time to time and it has indirectly increases the energy consumption of electricity. Ventilation nowadays is the best embodiment, zero consumed of electricity which is very eco-friendly system that provides natural air freshening ventilation system that will be able to reduce the consumption of the electricity usage especially in the residential and building area. Currently, there are 3 types of ventilation, which are natural ventilation, mechanical ventilation and hybrid ventilation. The basic theory of air ventilation is the process of involving two processes, which is infiltration and exfiltration of air. Infiltration in this study can be defined as the air moving to a conditional space inside the wall and these was the main focused. While exfiltration means is the hot air inside moving to the outside through the ventilation walls. Currently, the usages of ceramic ventilation block are less practical to used and lack of the scientific research on ceramic ventilation blocks. This research is to study the potential of ceramic stoneware ventilation wall created from extruding technique as conceptual modem ventilation wall taking consider of residency house. The methodology of this research contains 3 phases, which is process in to the study on literature review, material investigation, design development and fabrication. At the early phase this research studying on ventilation system, which is on its mechanism of the ventilation system, the design of ventilation, method to producing the ventilation system and identifying the suitable testing conducted. Phase two is investigation on material, which is by using the modified stoneware clay body, conducting the testing of the physical properties of the stoneware body and exploring the design through the morphological chart. Third phase by fabricating and evaluation phase. At the end of this research the ventilation blocks was created with using the stoneware clay and the new design of the ventilation block has been produce. From this study, we obtained stoneware body with 10 % CaC03 and as fired at 1100 °C was suggested as ventilator materials due to its low fired shrinkages of 7.38 % with acceptable MOR strength of 18.75 N/mm2 and water absorption of 6.5 %. It was successfully integrated to the air existing ventilation system via developed morphological chart. A prototype was sintered with 1100 °C and attached to the cements blocks which complied with basic requirements of Malaysian standard guidelines.